Against utilitarianism in animal testing law - Eva Bernet Kempers (Journal of Animal Law, Ethics and One Health)
Abstract. Despite the growing body of law that regulates the use of non-human animals for scientific purposes (shortly ‘animal testing law’) and the introduction of the principle of 3R’s as central guideline for policies addressing the practice, the ‘standard algorithm’ underlying the legal approach to laboratory animals has remained relatively consistent over the years. In order to determine whether or not experiments involving animals are allowed, decision-makers engage in a balancing practice in which they weigh the human benefits of animal testing against the harm and suffering that is being caused to animals. In this article, I will critique this ‘standard algorithm’ of animal testing law, arguing that it undermines the implementation of the 3R-principles. Exploring non-utilitarian ways of thinking about animals in a laboratory setting based on ‘the animal turn’, the article proposes some recommendations for how to think differently about lab animals, providing a starting point to a multi-dimensional legal approach to the use of animals for scientific purposes.